Using HCAHPS data to improve hospital care quality. Issue 6 (10th October 2016) - Carter, John C.; Silverman, Fred N.
Abstract : Purpose: The purpose of this paper is twofold: to enable hospital administrators to increase reimbursement rates under value-based purchasing (VBP) by understanding the process by which the Centers for Medicare and Medicaid Services (CMS) calculate and use performance scores from the Hospital Consumer Assessment of Healthcare Providers and Systems survey of patient experience; to apply statistical methods to determine what dimensions of patient care have the greatest impact on overall satisfaction scores and thus reimbursement. Design/methodology/approach: The expository purpose was met by locating, analyzing and interpreting published CMS documentation related to VBP to explain the complex methods used to convert raw survey data to total patient satisfaction scores on seven dimensions. The raw data on 2, 984 hospitals were cleaned and correlation and regression analysis used to measure the relationship between raw survey scores and overall patient satisfaction scores. Finally, Pareto analysis was used to show the relative influence of each dimension on satisfaction performance scores. Findings: Nursing communications accounted for 75 percent of the variance in the patient satisfaction domain score in a stepwise regression. Research limitations/implications: This research focusses only on the patient satisfaction component of VBP, over which hospital administrators have significant control. Future research could explore how hospital management can improve scores on clinical outcomes, process and efficiency. Practical implications: Shows hospital management the most influential methods for improving their patient satisfaction scores and reimbursement under VBP. Originality/value: Offers a managerially focussed explanation of how patient satisfaction scores are computed from raw survey data and how statistical analysis of the data can be used to improve quality.